2007
DOI: 10.1007/s00117-007-1559-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyse der mehrphasigen 64-Zeilen-Multidetektor-Computertomographie zur präoperativen angiographischen Evaluation potenzieller Lebendnierenspender

Abstract: The findings recorded in this study indicate that noninvasive preoperative planning with 64-row multidetector CTA and CTU is a reliable "one-stop shopping" method of examination for potential living kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Numerous studies have shown that CTA and CTU have a similar accuracy for the evaluation of anatomical features of the kidney and collecting system when compared to intraoperative findings. [ 24 25 26 27 ] The results of this study are also in accordance with the findings of the mentioned studies.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have shown that CTA and CTU have a similar accuracy for the evaluation of anatomical features of the kidney and collecting system when compared to intraoperative findings. [ 24 25 26 27 ] The results of this study are also in accordance with the findings of the mentioned studies.…”
Section: Discussionsupporting
confidence: 91%